Voluntary Disclosure of Evaded Taxes - Increasing Revenues, or Increasing Incentives to Evade? - Dominika Langenmayr (Center for Economic Studies and ifo Institute (CESifo), 2015)
Many countries apply lower fines to tax evading individuals when they voluntarily disclose the tax evasion they committed. I model such voluntary disclosure mechanisms theoretically and show that while such mechanisms increase the incentive to evade taxes, they nevertheless increase tax revenues net of administrative costs. I confirm the importance of administrative costs in a survey of German competent local tax authorities. I then test the effects of voluntary disclosure on the tax evasion decision, using the introduction of the 2009 offshore voluntary disclosure program in the U.S. for identification. The analysis confirms that the introduction of voluntary disclosure increases tax evasion.
Keywords: H26; K42; H24; 330; tax evasion; voluntary disclosure; self-reporting